Household Level Determinants of Agroforestry Practices Adoption in Rural Ethiopia. Issue 3 (3rd July 2019) - Beyene, Abebe D.; Mekonnen, Alemu; Randall, Bluffstone; Deribe, Rahel
ABSTRACT: Agroforestry is increasingly promoted as an economically and environmentally sustainable land use system. Understanding factors affecting smallholder farmers' decision to adopt agroforestry technologies and intensity of adoption is thus considered critical for the development of agroforestry. This research attempts to analyze and understand why agroforestry technologies are not being taken up more by examining household level factors that could influence the adoption of agroforestry technologies. We estimate Heckman selection model using household level data collected from different regions of rural Ethiopia. Our findings show that the age of the household head, land size, tenure insecurity, and proximity to towns have a significant effect on the probability of adopting. They also show that, once adoption decision had been taken, the area devoted to agroforestry technologies is influenced by household characteristics such as gender of the household head, land size, and proximity to towns. We also identify important measures that could help promoting agroforestry technologies in rural Ethiopia. Our findings may also provide scientific evidence for other similar countries whose livelihood depends mainly on agriculture and natural resources such as forests.